A Case Report of Pulmonary Malignant Melanoma with Multiple Intracranial Hemorrhagic Metastases - Zhang J; Yang G; Peng S; Fang Y (Cancer Management and Research)
Jian Zhang,1,2,* Guangming Yang,3,* Shaopeng Peng,1 Yuan Fang4 1Department of Neurosurgery, Gusu Provincial Hospital, Lanzhou, 730000, People’s Republic of China; 2NHC Key Laboratory of Diagnosis and Therapy of Gastrointestinal Tumor, Lanzhou, 730000, People’s Republic of China; 3The First Clinical School of Medicine, Gansu University of Traditional Chinese Medicine, Lanzhou, 730000, People’s Republic of China; 4Department of Ultrasonography, Gusu Provincial Hospital, Lanzhou, 730000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuan Fang, Email 18189694292@163.comAbstract: Primary pulmonary malignant melanoma is a very rare non-epithelial tumour with a high degree of malignancy, susceptibility to early haematogenous metastasis and poor prognosis. Lung malignant melanoma with multiple intracranial metastases is highly susceptible to misdiagnosis or underdiagnosis in clinical practice. This article reports a case of pulmonary malignant melanoma with multiple intracranial hemorrhagic metastases, aiming to improve clinicians’ understanding of this disease through this case analysis. Especially for patients over 60 years old with intracranial multiple hemorrhage, it is necessary to broaden the diagnostic and therapeutic thinking, and to exclude rare malignant tumors in the whole body through multi-systematic examination, so as to avoid misdiagnosis or omission of the diagnosis, which may cause delays in the condition.Keywords: malignant melanoma of the lung, metastases, malignant tumours, haemorrhagic stroke